GE_GERICHTE C/14845/2018 vom 25. Juni 2019 - GE Cour de justice (2019)
MESURE PROVISIONNELLE;CONDITION DE RECEVABILITÉ;COMPÉTENCE;CHANGEMENT DE RÉSIDENCE;AUTORITÉ PARENTALE | CPC.59.al1; CPC.60; CC.296.al2; LDIP.10; CLaH96.5; LDIP.85.al1; LDIP.82; CL.5.let2